Discovering The Determinants of Motivation, Compensation, Workload on Employee Performance - Siagian, Ester Mawar; Elizabeth, Elizabeth; Budiyanto, Sarah Khairunnisa; Saputra, Eka Kurnia; Machin, H. (International Journal of Economics Development Research (IJEDR), 2024)
Research to test the influence of motivation, compensation, workload on the work performance of CV ABCD employees in Jakarta. This research uses a quantitative method with multiple linear regression analysis. Data were collected using a questionnaire given to all CV ABCD employees in Jakarta. The sampling technique used a census sampling technique with a population of 56 employees. The results of the research show partially and simultaneously the variables of motivation, compensation, workload on the work performance of CV ABCD employees in Jakarta. These findings can be a reference for CV ABCD in Jakarta to improve employee performance which has a good impact on the success of the company.